Materiality Judgments and the Resolution of Detected Misstatements: The Role of Managers, Auditors, and Audit Committees - Keune, Marsha B.; Johnstone, Karla M. (The Accounting Review, 2012)
ABSTRACT This study investigates how manager and auditor incentives, along with audit committee characteristics, are associated with materiality judgments about detected misstatements. Using data on detected misstatements that occurred between 2003 and 2006, we find auditors' incentives to protect their reputations weaken the effect of managerial incentives associated with the pressure created by analyst following; auditors are less likely to allow managers to waive material misstatements as audit fees increase. Regarding audit committee characteristics, results reveal that audit committees with greater financial expertise are less likely to allow managers to waive material misstatements compared to audit committees with less expertise. Data Availability: Data used in the study are available from public sources.